Letter from George Hevesy to Georg Bredig - Hevesy, Georg von (1925)
Georg von Hevesy (1885-1966) thanks Georg Bredig (1868-1944) and expresses his desire to be mentored by Bredig. Georg von Hevesy was a Hungarian chemist. He worked in inorganic and nuclear chemistry at Stockholm University. In 1923, he co-discovered the element hafnium. He received the Nobel Prize in Chemistry in 1943 for his contribution to the development of radioactive tracers. At the time this letter was written, Hevesy was a professor of physical chemistry at the University of Freiburg.
Keywords: Hevesy, Georg von, 1885-1966; Bredig, Georg, 1868-1944; Hafnium; Nobel Prize winners; Germany--Freiburg im Breisgau; Nordisk institut for teoretisk fysik; Chemistry, Physical and theoretical